نظام حاسوبي لتكامل تقدير (الكلف والكميات) و الجدولة الزمنية لمشاريع التشييد - حسن بسام; نجا هاني; غانم الأعصم (Latakia University Journal -Engineering Sciences Series, 2019)
غالبا ما تتم عمليات حسابات الكميات (Quantity Take-Off) بشكل منعزل عن الجدولة الزمنية (Scheduling) وغالبا ما تتم ببرمجيات منفصلة عن برمجيات الجدولة الزمنية. إضافة إلى أن عملية الجدولة الزمنية غالبا ما تتم باستخدام طرق الشبكات كطريقة المسار الحرج (CPM) والتي تصبح معقدة وصعبة من أجل المشاريع ذات الطبيعية التكرارية. يقدم هذا البحث نظام يهدف إلى تكامل عمليتي تقدير الكميات والجدولة الزمنية مما يختصر الكثير من الزمن اللازم لإنجاز التخطيط للمشروعات ويجنب المخطط الوقوع في الخطأ أثناء الانتقال من نتائج برامج حساب الكميات ونقلها كمدخلات إلى برامج الجدولة الزمنية. كما يوفر المستخدمين قليلي الخبرة في مجال التخطيط الزمني للمشروعات أداة تزيل معظم المصاعب التي يوجهها العاملين في مجال تخطيط المشروعات. يميز النظام بين نوعين من الأنشطة, الأنشطة المنفصلة وتتم معالجتها بطريقة المسار الحرج, والأنشطة ذات الطبيعة التكرارية وتتم معالجتها بطريقة الجدولة الخطية (LSM) بما يضمن استمرارية عمل الأطقم ضمن الأقسام المتكررة. Quantities take-off and time scheduling processes are usually performed separately and done by different software. Moreover, time scheduling process is usually performed using network methods like critical path method (CPM) which became very complex and different in the projects which have activities of a repeated nature. This paper introduces a system that aims at integrating quantities estimating and time scheduling processes for multi-story buildings projects. This integration reduces the required time to plan projects and keeps the planner away from committing mistakes during the transfer of the quantities take-off software outputs into time scheduling software as inputs. It also provides for less experiences users of project time scheduling means of eliminating most of the problems that encounter the project planner. The proposed system distinguishes between two kinds of activities: direct activities which are scheduled by critical path method and repetitive activities which are scheduled by linear scheduling method (LSM) to maximize the utilization by achieving the work continuity in the repetitive units.